An emotional approach to beef evaluation. (May 2017) - Borgogno, Monica; Cardello, Armand V.; Favotto, Saida; Piasentier, Edi
Abstract: The emotions associated with beef consumption, the influence of breeding system information on emotions ("Conventional" - C vs "Only from the Italian Simmental" – OIS label) and their relationship with liking were evaluated by 93 meat consumers. Respondents were asked to evaluate the same samples of Italian Simmental meat provided with the two different labels. Liking scores were obtained using a 9-point scale and the emotions from the EsSense25 list were scored on 5-point scale (1 = "not at all", 5 = "extremely"). A positive and significant effect of OIS information was highlighted on liking scores. Moreover, the breeding system information significantly affected 22 out of the 25 emotions. OIS label elicited higher positive and lower negative feelings about the meat than did the C label. Providing the same beef with different breeding information led to different emotions being evoked in consumers, and these differences in emotions were associated with different levels of liking for beef. Highlights: Only Italian Simmental (OIS) breeding system information effect was evaluated. OIS information increases beef liking. OIS information evokes an overall improvement of beef emotional performance. Emotions were correlated to OIS liking as a function of valence.